Moral reasoning in the context of reform: a study of Russian officials - Stewart, Debra W.; Kem, Jackie D.; Sprinthall, Norman A. (2002)
This article reports on an exploratory study of ethical reasoning among public administrators in Russia. Survey interviews and focus group follow-ups with civil servants participating in graduate training programs at the Russian Academy of Public Service provide information about their preferred mode of ethical reasoning; the demographic, attitudinal, organizational, and professional factors associated with that reasoning; and the behavioural choices implied. Using a sample of 113 public officials who represent a broad spectrum of regions in Russia, this study assesses moral reasoning, examines variables associated with alternative model, and compares these responses with findings from studies conducted in Poland and the United States. Based on this exploratory study, we suggest implications for theory, research, and practice. - Reproduced.
Keywords: Civil service - Russia; Civil service